2021
DOI: 10.1038/s41598-020-79110-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and levodopa induced dyskinesia in Parkinson’s disease: a longitudinal study from the PACOS cohort

Abstract: Aim of the study was to evaluate possible associations between cognitive dysfunctions and development of Levodopa Induced Dyskinesia (LID). PD patients from the Parkinson’s disease Cognitive impairment Study cohort who underwent a baseline and follow-up neuropsychological evaluations were enrolled. Mild Cognitive Impairment (PD-MCI) was diagnosed according to MDS level II criteria. The following cognitive domains were evaluated: episodic memory, attention, executive function, visuo-spatial function and languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…We conducted additional analyses for motor complications using daily levodopa dose as a variable instead of LEDD ( Supplementary Table 4 and 6 in the online-only Data Supplement) based on these previous studies that reported a higher levodopa dose as a risk factor for motor complications [ 38 , 39 ]. The association of visuospatial dysfunction with levodopa-induced dyskinesia in our study lacks evidence, which is inconsistent with the result of one previous study that reported impairment of attention and executive function as a risk factor for levodopa-induced dyskinesia [ 40 ]. Additional research is needed with a longer observation period, including sufficient cases of the occurrence of motor complications.…”
Section: Discussioncontrasting
confidence: 99%
“…We conducted additional analyses for motor complications using daily levodopa dose as a variable instead of LEDD ( Supplementary Table 4 and 6 in the online-only Data Supplement) based on these previous studies that reported a higher levodopa dose as a risk factor for motor complications [ 38 , 39 ]. The association of visuospatial dysfunction with levodopa-induced dyskinesia in our study lacks evidence, which is inconsistent with the result of one previous study that reported impairment of attention and executive function as a risk factor for levodopa-induced dyskinesia [ 40 ]. Additional research is needed with a longer observation period, including sufficient cases of the occurrence of motor complications.…”
Section: Discussioncontrasting
confidence: 99%
“…In our present investigation, we corroborated these findings, reaffirming the significant association between dyskinesia and disease duration, LEDD, UPDRS II and MoCA scores. This conveys that dyskinesia arises not solely from medication usage but is intricately intertwined with disease severity and cognitive functioning [ 28 ]. In addition to these well-established insights, our study unearthed a compelling revelation—a notable surge in the incidence of moderate to severe OAB symptoms, encompassing urinary frequency, urgency, and nocturia, among PD patients grappling with dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…Tremor, bradykinesia, dyskinesia, and cognitive deficits are among the motor and non-motor symptoms seen in patients with disorders of dopaminergic neurotransmission such as Parkinson’s disease and neurotoxicant-induced parkinsonism ( Zhu et al, 2011 ; Luca et al, 2021 ). In vivo electrophysiology can be used to elucidate the effects of altered dopaminergic neurotransmission on neural network activity.…”
Section: Current State Of the Art: Changes In Neural Network Activity...mentioning
confidence: 99%